PENGUATAN KEPRIBADIAN SISWA SMP BERBASIS AGAMA SEBAGAI ANTISIPASI DEGRADASI MORAL DI ERA DIGITAL - Firdaus, Ahmad; Ningrum, Siti Utami Dewi (Prosiding Temu Ilmiah Nasional Guru, 2023)
This study investigates the role of strengthening the personality of students at the junior high school (junior high school) level with a religious approach in facing the challenges of moral degradation arising from the development of globalization. Globalization has had a positive impact in terms of technological progress and the exchange of information, but it has also caused a shift in traditional values that can threaten individual morality, especially students at the junior high school level. In order for students to overcome this challenge, a comprehensive approach is needed that involves religious factors in strengthening their personality. Using a method with a descriptive-analytical approach this research utilizes relevant literature sources, such as journals, mass media news, and scientific books. The results of this study indicate that moral degradation is a serious challenge faced by the younger generation. For this reason, to strengthen the personality of religion-based students, various parties must be involved, starting from the family, school, and community.